Vaccinia virus modulates the redox environment by inhibiting reactive oxygen and nitrogen species with increased activity of endogenous antioxidant enzymes - Marília Bueno da Silva Menegatto; Ariane Coelho Ferraz; Rafaela Lameira Souza Lima; Pedro Henrique Guimarães; Oluwashola Samuel Ola-Olu; Pedro Alves Machado-Junior; Wellington Carvalho Malta; Thaís de Fátima Silva Moraes; Frank Silva Bezerra; Breno de Mello Silva; José Carlos de Magalhães; Jordana Grazziela Alves Coelho dos Reis; et al. (Scientific Reports)
Abstract The vaccinia virus (VACV) is the most studied and well-characterised member of the Poxviridae family. However, the mechanisms through which it modulates redox homeostasis in host cells remain unclear. Although oxidative stress, which is marked by elevated levels of reactive species, contributes to the pathogenesis of many viral infections, poxviruses may adopt distinct strategies. VACV has redox effector proteins that are released into the cytosol when the virus penetrates the host cell. This study demonstrates for the first time that VACV infection leads to the activation of the nuclear factor erythroid 2 (Nrf2)/antioxidant response element pathway, a key regulator of cellular antioxidant responses, a mechanism not previously described for any poxvirus. Using BSC-40 cells, we observed that VACV significantly reduced reactive oxygen and nitrogen species levels, downregulated inducible nitric oxide synthase, and enhanced the activity of antioxidant enzymes, such as superoxide dismutase, catalase, and glutathione peroxidase. This antioxidant shift is correlated with increased Nrf2 activity and the upregulation of its downstream targets. This virus-induced antioxidant state may be an immunomodulatory mechanism that facilitates viral replication by dampening host defence. Thus, our findings expand the current understanding of virus–host interactions in poxvirus infections.